Spectrophotometric determination of lansoprazole in pharmaceuticals using bromate-bromide mixture based on redox and complexation reactions - Basavaiah, Kanakapura; Ramakrishna, Veeraiah; Anilkumar, Urdigere Rangachar; Somashekar, Bankavadi Chikkaswamy (Eclética Química, 2007)
Two sensitive spectrophotometric methods are described for the determination of lansoprazole (LPZ) in bulk drug and in capsule formulation. The methods are based on the oxidation of lansoprazole by insitu generated bromine followed by determination of unreacted bromine by two different reaction schemes. In one procedure (method A), the residual bromine is treated with excess of iron (II), and the resulting iron (III) is complexed with thiocyanate and measured at 470 nm. The second approach (method B) involves treating the unreacted bromine with a measured excess of iron (II) and remaining iron (II) is complexed with orthophenanthroline at a raised pH, and measured at 510 nm. In both methods, the amount of bromine reacted corresponds to the amount of LPZ. The experimental conditions were optimized. In method A, the absorbance is found to decrease linearly with the concentration of LPZ (r = -0.9986) where as in the method B a linear increase in absorbance occurs (r = 0.9986) The systems obey Beer’s law for 0.5-4.0 and 0.5-6.0 μg mL -1 for method A and method B, respectively. The calculated molar absorptivity values are 3.97μ10 4 and 3.07μ10 4 L mol -1 cm -1 for method A and method B, respectively, and the corresponding Sandell sensitivity values are 0.0039 and 0.0013 μg cm -2.